The Effect of Counseling About SADARI with Demonstration Methods on WUS Skills (Women of Childbearing Age) - Sabda Nirwana, Betanuari; Khofidhotur Rofiah; Alfika Awatiszahro; Sri Mulyani; Hesti Rahayu (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Breast cancer is one of the most common types of cancer suffered by women with a very high prevalence in all countries in the world. In Indonesia, breast self-examination is still individual so early detection programs are still not efficient and effective. The lack of education about early detection of breast cancer can result in patients with advanced breast cancer being still quite hiFindfind the early symptoms of breast cancer, women can detect it themselves, so there is no need for an expert to find the beginning of breast cancer.The purpose of this study was to analyze the effect of counseling using the conscious demonstration method on the skills of women of childbearing age, the SPSS test used by Wilcoxon with the results after being given awareness counseling using the demonstration method, 93.3% of respondents had better skills, the results of data analysis were p-value < 0.05, the results of the study showed that there was an effect of counseling on Safari with the demonstration method on Sadari skills in women of childbearing age. It is hoped that all women of childbearing age can improve Sadari skills to detect breast cancer early.